The Principle of Justice in the Obligations of Management and Shareholders of Corporate Taxpayers for Tax Debts and Tax Collection Costs of Corporate Taxpayers - Meco Sitardja (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study examines the application of the principle of justice in determining the obligations of corporate taxpayers' managers and shareholders for tax debts and tax collection costs. The main problem in this study is the expansion of responsibility from legal entities to individual legal subjects, namely managers and shareholders, in the tax collection process. This raises questions about the extent to which the principle of justice is applied in assigning such responsibilities, considering that corporate law applies the principles of separate legal entity and limited liability. This study uses a normative juridical method with a statutory and conceptual approach and secondary supporting data. The results of the study indicate that managers can be held accountable for tax debts if proven to have violated their fiduciary duties or committed negligence in managing the company. Meanwhile, shareholders are essentially not personally liable, except in certain circumstances such as abuse of legal entity through the application of the doctrine of piercing the corporate veil. The results of the study indicate that the application of the principle of justice in determining the obligations of managers and shareholders must be based on the principles of fault, proportionality, and actual involvement, so as not to result in an excessive expansion of responsibility. Thus, the principle of justice acts as a normative boundary in maintaining a balance between the state's interests in tax collection and legal protection for legal subjects in companies.